Making the connection : data-informed practices in academic support centers for college athletes - Comeaux, Eddie (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
Making the Connection: Data-Informed Practices in Academic Support Centers for College Athletes is practical and ideal for those who seek to use research to inform their individual and organizational practices. This volume is primarily intended for upper-level undergraduate and graduate students, though scholars, researchers, teachers, practitioners, coaches, athletics administrators, and advocates of intercollegiate athletics will also find it useful. It comprises a series of chapters that cover a wide range of evidence-based approaches designed to enhance the practices of those who work closely with college athletes. Given the breadth of the field overall, this single volume is not exhaustive, but the current concerns, challenges, and themes of relevance to higher education researchers, practitioners, and others are well addressed.The intent of the text is to spark conversation about how college and university constituents can reframe their thinking about the importance of innovative research to careful, informed practice. Likewise, the contributors hope that it will inspire greater awareness and action among practitioners, as well as advance scholarship in the area of athletics. Each chapter includes current research, and in some cases theoretical perspectives, which should assist practitioners enhance the well-being of college athletes. Each chapter also offers guided discussion questions that are ideal for use as the basis of further conversation in the classroom setting.Adopters of this text will benefit from leading voices in the field who delve into complex issues, shedding new light and presenting unique opportunities for understanding a diversity of perspectives on evidence-based practices in support centers for athletes. In all, this volume provides a rich portrait of data-driven practices designed to assist practitioners and others who work closely with college athletes, and lays the groundwork for an ambitious and long overdue agenda to further develop innovative research that informs the practices of athletics stakeholders and improves the quality of experiences for college athletes.
Keywords: College athletes -- Education -- United States.; Education, Higher -- Aims and objectives -- United States.; Education -- Aims & Objectives.; Higher education, tertiary education.; Educational strategies and policy.; elektronické knihy; electronic books